An ethical reflection on drug use in eSport - Sungjoo Park; Dayoun Lim; Jinhee Kim (Korea Institute of Sport Science, 2020)
Purpose Highly popular these days, eSport is inviting increasing scholarly attention and research. Scholarly work on eSport, however, remains focused on whether eSport is a "real" sport, that is, its sporting qualities and status, excluding ethical issues. This paper analyzes ethical issues about cognitive enhancement drugs often associated with eSport in order to suggest guidelines for resolving these issues. Methods First, environmental features of eSport are examined to find out types of cheating in eSport, as well as the ways eSport athletes are exposed to drugs. Next, ethical issues of cognitive enhancement drug use and why they are important are discussed, drawing upon multiple scholars. Last, this paper argues that the ban on drug use conventionally implemented in sport is not appropriate to eSport due to the characteristics of eSport. The paper concludes with possible future approaches to this issue. Results The ban lists administered by ESIC and WADA would not work for the need of eSport athletes and even run a risk of stunting the growth of eSport industries. It is thus important to think up an appropriate drug-related policy for eSport. Preemptive education for eSport athletes is also required to promote the ethical consciousness and judgment regarding drug use. Conclusions Insofar as eSport's huge popularity leads to the increased status of eSport athletes, thereby exerting much influence on young people, ethical questions about eSport, drug use in particular, need to be urgently discussed for the sake of eSport's wholesome development.